Directions for improving the legal regulation of forensic DNA analysis in Ukraine in the context of integration into the European Union - R. L. Stepaniuk; V. V. Kikinchuk (Bulletin of Kharkiv National University of Internal Affairs)
An analysis of European standards and main trends in the field of legal regulation of forensic DNA analysis has been carried out. It has been established that the general European legislation defines recommendations on the general principles of using DNA analysis within the framework of the criminal justice system, establishes the obligation of each state to create and maintain a national DNA database, exchange information based on DNA databases, take measures to protect personal data, store DNA profiles of persons convicted of sexual offenses against children, to accredit forensic laboratories to ensure the proper quality of molecular genetic research. Taking into account the experience of European countries, it can be seen that a comprehensive approach to the improvement of domestic legislation, namely the implementation of the law on the national DNA database, the introduction of amendments and additions to the current Code of Criminal Procedure of Ukraine, other laws and departmental regulations regarding the use of DNA analysis in criminal proceedings, is a necessary prerequisite for bringing this area of law enforcement to a new qualitative level.